Analisis Pengaruh Profitabilitas, Pengungkapan Corporate Social Responsibility Dan Corporate Governance Terhadap Nilai Perusahaan (Studi Empiris: Pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Periode 2010-2013) - Hartoyo, Hartoyo, Drs. Agus Endro Suwarno, M.Si (2016)
This research aimed to analyze the influence of Profitability, Corporate Social Responsibility, and Corporate Governance pervade Managerial Ownership, Institutional Ownership and Independent Commisioners to firm value in banking company which listed in Indonesian Stock Exchange period 2010- 2013. The population used in this study are all banking company which listed in Indonesian Stock Exchange period 2010- 2013. The study used purposive sampling method to collect the sample. The number of samples collected as many as 9 companies with 36 data. The collected data were analyzed using data analysis first conducted classical assumption test before hypothesis test. Testing the hypothesis in this study using multiple regression analysis with t-test, f-tets and the coefficient of determination. The results showed that the coefficient of determination obtained a value of 0,492, whict means that 49,2% firm value is affected Profitability, Corporate Social Responsibility, Managerial Ownership, Institutional Ownership and Independent Commisioners the balance of 50,98% is influenced by other variables outside the research. Hypotesis test results showed that the Profitability, Corporate Social Responsibility and Independent Commisioners have significant effect on firm value, while the Managerial Ownership and Institutional Ownership have not significant affect on firm value.